2002
DOI: 10.1093/toxsci/68.2.429
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Gap Junctional Intercellular Communication by Perfluorinated Compounds in Rat Liver and Dolphin Kidney Epithelial Cell Lines in Vitro and Sprague-Dawley Rats in Vivo

Abstract: Gap junctional intercellular communication (GJIC) is the major pathway of intercellular signal transduction, and is thus important for normal cell growth and function. Recent studies have revealed a global distribution of some perfluorinated organic compounds, especially perfluorooctane sulfonic acid (PFOS) in the environment. Because other perfluoroalkanes had been shown to inhibit GJIC, the effects of PFOS and related sulfonated fluorochemicals on GJIC were studied using a rat liver epithelial cell line (WB-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
116
0
9

Year Published

2004
2004
2015
2015

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 211 publications
(131 citation statements)
references
References 34 publications
6
116
0
9
Order By: Relevance
“…The doses (1, 10, and 100 µM) of PFCs were administrated according to previous literature (7,14). Primary hippocampal neuron cultures and acute hippocampal slices from SpragueDawley rats were prepared as described previously (15,16).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The doses (1, 10, and 100 µM) of PFCs were administrated according to previous literature (7,14). Primary hippocampal neuron cultures and acute hippocampal slices from SpragueDawley rats were prepared as described previously (15,16).…”
Section: Methodsmentioning
confidence: 99%
“…Evidences showed that PFOS accumulates up to 1-10 mg/kg (approximately 2-20 µM) in some animal tissues (1) and 1.82 µM in serum of occupational workers (4). The potential toxicity of PFOS, such as hepatotoxicity, interference with mitochondrial bioenergetics, impeding intercellular communication through gap junctions, endocrine dysfunction, effects on development and reproduction, and carcinogenicity, has been documented (3,6,7). A previous study revealed that PFOS accumulates in rat brain after subchronic exposure (6).…”
Section: Introductionmentioning
confidence: 99%
“…The U. S. Environmental Protection Agency has expressed concern over effects of these types of compounds, due to their potential for accumulation and toxicity to humans and wildlife (3). Perfluorocarboxylic acids (PFCAs) are peroxisome proliferators (4) as well as tumor promoters (5) and may inhibit gap junction intercellular communication at environmentally relevant concentrations (5).…”
Section: Introductionmentioning
confidence: 99%
“…Known in vivo effects of perfluorochemical exposure are an increase of the relative liver weight in the rat, mouse, and cynomolgus monkey and the induction of peroxisomal fatty acid β-oxidation and effects on several biochemical end points related to oxidative stress in the rat and mouse (Ikeda et al 1985(Ikeda et al , 1987Permadi et al 1992Permadi et al , 1993Sohlenius et al 1993). Other documented effects are the induction of hypolipemia in the rat, mouse, and cynomolgus monkey (Haughom and Spydevold 1992;Lau et al 2001;Seacat et al 2002) and the inhibition of gap junction intercellular communication (Hu et al 2002) and effects on carboxylesterase expression in the rat (Derbel et al 1996). Developmental and maternal effects in the rabbit, rat, and mouse (Lau et al 2001;York et al 2000) and promotion of carcinogenesis in the rat (Abdellatif et al 1990) have also been reported.…”
mentioning
confidence: 99%